2018
DOI: 10.1039/c7ra13480k
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid-derived anisotropic silver nanoparticles inhibit growth and change the expression of virulence genes in Escherichia coli SM10

Abstract: We hereby present a novel greener and ecofriendly synthesis of anisotropic silver nanoparticles (AgNPs) using water soluble quercetin diphosphate (QDP). QDP was employed as a reducing, capping and stabilizing agent at room temperature without any extraneous reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…However, smaller and round-shaped nanoparticles (1–4 nm) were found to be in higher densities than the long sheets of Pep-AgNPs (40–80). A similar distribution was observed by the flavonoid-derived anisotropic silver nanoparticles [ 29 ]. The different shape and size of the Pep-AgNPs are mainly due to the peptone chemical composition.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, smaller and round-shaped nanoparticles (1–4 nm) were found to be in higher densities than the long sheets of Pep-AgNPs (40–80). A similar distribution was observed by the flavonoid-derived anisotropic silver nanoparticles [ 29 ]. The different shape and size of the Pep-AgNPs are mainly due to the peptone chemical composition.…”
Section: Resultssupporting
confidence: 79%
“…The TEM image showed a combination of long sheets and very small round-shaped Pep-AgNPs nano-particles. The anisotropic morphology shows different sizes and various shapes of the nanoparticle [ 27 , 28 , 29 ]. Therefore, the obtained TEM image corroborated that Pep-AgNPs has anisotropic particle morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that AgNPs derived from phosphorylated flavonoids exhibited excellent antibacterial activity [25,51]. In addition to size, the shape also showed the importance of similar-sized LTP-AgNPs, where quasi-spherical LTP-AgNPs showed higher capability (LTP-AgNP5) than corresponding similar-sized spherical ones.…”
Section: Discussionmentioning
confidence: 92%
“…The synthesized Ag NPs demonstrated a reducing effect on the swarming behaviour of E. coli, P. aeruginosa PAO1, and K. pneumoniae [80]. Also, Ag NPs showed to have reduced about 98% activity of the swarming motility associated with the arresting effect in the expression of fliL flagellar gene in E. coli [81]. The swarming movement was the reason of combination sensory transduction and universal control operations.…”
Section: The Impact Of Nanoparticles On Swarming Phenomenonmentioning
confidence: 91%